Are tanning salons in compliance with German law? An evaluation based on a nationwide representative survey - Goerig, Tatiana; Schneider, Sven; Greinert, Ruediger; Breitbart, Eckhard W.; Diehl, Katharina (Photodermatology Photoimmunology & Photomedicine, 2018)
Background: Given the evidence for increased skin cancer risk due to the sunbed use, a regulation of hazardous artificial ultraviolet radiation (UVR regulation) was passed in Germany in 2012. The aim of this study was to explore the advisory services in tanning studios as reported by sunbed users and to evaluate the information provided by the personnel of tanning salons after the UVR regulation was enacted. Methods: The first wave of the representative National Cancer Aid Monitoring on Sunbed Use included a subgroup of 357 German citizens between 14 and 45 years who had used sunbeds since the UVR regulation was implemented. The participants provided data on sunbed use and related issues in telephone interviews. Results: Although sunbed operators are mandated to offer their customers certain services at least once since the implementation of the UVR regulation, 15.4% of sunbed users were never advised to use protective eyewear during tanning and 13.1% were not provided with eyewear during their last sunbed use. Overall, 66.0% were never offered to develop a tanning schedule, 56.9% were never advised on the risks of UVR, 43.4% were never offered a determination of their skin type and 40.0% of users were never advised on how to use a sunbed safely. Conclusions: The data showed that 3 years after the UVR regulation was enacted, compliance with this legislation is still not optimal. Binding wording in the legal text and making them applicable to unsupervised sunbeds as well is necessary to extend the impact of this legislation.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Germany; legal aspects; sunbed use; tanning